CLINICAL CHARACTERISTICS, OUTCOMES, & MORTALITY IN PREGNANT WOMEN WITH COVID-19 - RANA, MA; SIDDIQI, MRO; SIDDIQUI, MH; ARIF, B; PERVAIZ, R; AWAD, AHA; RAZA, S (Biological and Clinical Sciences Research Journal, 2023)
The COVID-19 pandemic has significantly impacted global health, with pregnant women being identified as a vulnerable population. As the pandemic continues, there is a need to understand the clinical characteristics, outcomes, and mortality rates of pregnant women with COVID-19 to inform clinical decision-making and optimize care. This study aims to evaluate the clinical characteristics, outcomes, and mortality in pregnant women with COVID-19. The retrospective cohort analysis was conducted at the Bahria town international hospital Lahore and Family care hospital, Karachi from September 17, 2020, to September 30, 2021. A total of 109 records were evaluated. 69 patients infected with covid-19 diseases and had mid to moderate symptoms were included for further analysis. From the medical record, the data regarding the severity of the disease, clinical presentation at the time of admission, including signs and symptoms, the outcome of the pregnancy, and the mortality of pregnant women were noted. The most common clinical characteristics, fever, cough, throat pain, and shortness of breath, were noted at admission after confirmation of COVID-19 infection in mild to moderate cases of pregnant women. The most common co-morbid conditions were anemia (65%), hypertension, and diabetes (4.5% and 3.5%, respectively). The most common outcome was pre-term delivery 12 (18%). In our study population, there was only one miscarriage. The mortality rate in our study was zero. All the patients were discharged alive from the hospital. Only 3 patients were shifted to ICU and discharged after recovery. The caesarian section was done in more than half of the study group. Based on the results, pregnant women with COVID-19 are at increased risk of adverse outcomes, including pre-term delivery, cesarean delivery, and admission to the ICU. Mortality was zero in our study. Early detection and management of COVID-19 in pregnant women are essential to improve maternal and fetal outcomes. Healthcare providers should continue to monitor and evaluate the clinical characteristics, outcomes, and mortality rates in pregnant women with COVID-19 to inform clinical decision-making and optimize care.